Dual UV irradiation-based metal oxide nanoparticles for enhanced antimicrobial activity in Escherichia coli and M13 bacteriophage - Jin SE (Dove Medical Press, 2017)
Su-Eon Jin,1 Woochul Hwang,2 Hyo Jung Lee,3 Hyo-Eon Jin3 1Research Institute for Medical Sciences, College of Medicine, Inha University, Incheon, 2ECOSET Co., Ltd., Ansan, 3College of Pharmacy, Ajou University, Suwon, Korea Abstract: Metal oxide (MO) nanoparticles have been studied as nano-antibiotics due to their antimicrobial activities even in antibiotic-resistant microorganisms. We hypothesized that a hybrid system of dual UV irradiation and MO nanoparticles would have enhanced antimicrobial activities compared with UV or MO nanoparticles alone. In this study, nanoparticles of ZnO, ZnTiO3, MgO, and CuO were selected as model nanoparticles. A dual UV collimated beam device of UV-A and UV-C was developed depending upon the lamp divided by coating. Physicochemical properties of MO nanoparticles were determined using powder X-ray diffractometry (PXRD), Brunauer-Emmett-Teller analysis, and field emission-scanning electron microscopy with energy-dispersive X-ray spectroscopy. Atomic force microscopy with an electrostatic force microscopy mode was used to confirm the surface topology and electrostatic characteristics after dual UV irradiation. For antimicrobial activity test, MO nanoparticles under dual UV irradiation were applied to Escherichia coli and M13 bacteriophage (phage). The UV-A and UV-C showed differential intensities in the coated and uncoated areas (UV-A, coated = uncoated; UV-C, coated << uncoated). MO nanoparticles showed sharp peaks in PXRD patterns, matched to pure materials. Their primary particle sizes were less than 100 nm with irregular shapes, which had an 8.6~25.6 m2/g of specific surface area with mesopores of 22~262 nm. The electrostatic properties of MO nanoparticles were modulated after UV irradiation. ZnO, MgO, and CuO nanoparticles, except ZnTiO3 nanoparticles, showed antibacterial effects on E. coli. Antimicrobial effects on E. coli and phages were also enhanced after cyclic exposure of dual UV and MO nanoparticle treatment using the uncoated area, except ZnO nanoparticles. Our results demonstrate that dual UV-MO nanoparticle hybrid system has a potential for disinfection. We anticipate that it can be developed as a next-generation disinfection system in pharmaceutical industries and water purification systems. Keywords: dual UV, metal oxide nanoparticles, antimicrobial activity, E. coli, M13 bacteriophage